Problem Base Learning (PBL) : Suatu Model Pembelajaran Untuk Mengembangkan Cara Berpikir Kreatif Siswa - Maya Agustina (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Education is essentially absolute terms for human resources to a better future. Problem Based Learning (PBL) is one of the learning models that demanding a mental activity of student to understand the concept of learning situations and problems presented. Through PBL, students can develop a possessed abilities such as innovative creative and critical thingking. Creative thingking means thought process that is able to give different ideas then become new knowledge and answer needed. Creative thingking also gives many possible answer based on information given by accentuation on diversity and suitability answers. Learning with PBL can develop a student’s creative thinking ability. In PBL, student are charged to afford to finish their own problems and work independently so that students can develop their creative thingking. In addition, students can be trained develop higher-order thingking ability and creative mindset.